Role of argon laser trabeculoplasty as primary and secondary therapy in open angle glaucoma in Indian patients. Issue 7 (1st July 2002) - Agarwal, H C; Sihota, R; Das, C; Dada, T
Abstract : Aims: To study the efficacy of argon laser trabeculoplasty (ALT) as a primary and secondary therapy in Indian patients with primary open angle glaucoma (POAG). Methods: ALT was performed as a primary therapy in 40 eyes of 21 patients newly diagnosed with POAG (group I) and as a secondary therapy in 39 eyes of 21 patients who had been taking topical antiglaucoma medications for more than 1 year. The best corrected visual acuity, baseline intraocular pressure (IOP), diurnal variation of IOP, anterior chamber angles, and visual fields were the various parameters evaluated before and after performing ALT. Follow up visits were scheduled at 24 hours, 1 week, 1 month, 3 months, 6 months, and 1 year after the surgery. The patients were recalled at the end of 5 years for the final follow up examination. Success of ALT was defined as IOP ≤21 mm Hg without any medication with no progression of disc or visual field changes. Results: The prelaser mean IOP was 25.8 (SD 3.4) mm Hg in group I and 26.1 (3.2) mm Hg in group II. The mean post-laser IOP at 5 year follow up was 18.1 (3.2) mm Hg in group I and 22.7 (3.9) mm Hg in group II (p= 0.002) while the mean reduction in IOP was 5.7 (1.8) mm Hg in group I and 3.2 (0.8) mm Hg in group II (p<0.001). The diurnal variation reduced from a preoperative value of 7.9 (1.4) mm Hg to 3.6 (1.3) mm Hg in group I and from 7.7 (1.4) mm Hg to 5.8 (1.8) mm Hg in group II (p<0.001). The success rate of ALT was 75% at 1 year and 65% at 5 years in group I and 35% at 1 year and 10% at 5 years in group II. Conclusion: ALT can be used as a primary therapy in pigmented eyes with POAG. ALT is less effective as a secondary therapy in controlling the IOP in eyes of patients on long term topical antiglaucoma treatment.